1994
DOI: 10.2105/ajph.84.8.1307
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and demographic predictors of illicit and licit drug use among lesbians and gay men.

Abstract: Studies on illicit and licit drug use among homosexuals of both sexes have focused primarily on gay men, used limited drug measures, and been conducted in cities known for large homosexual populations. This paper examines (1) the prevalence of 12 illicit and licit drugs by sex and age group and (2) the demographic predictors of past-year frequency of marijuana, alcohol, and cigarette use. Organizational mailing lists were used to collect self-report data on 455 homosexuals living in a southern state. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 15 publications
5
67
1
Order By: Relevance
“…Among men solicited from mailing lists provided by gay organizations, 40% reported smoking during the previous year, which was associated with less education. 6 Among bar and telephone-recruited MSM in Oregon and Arizona, 48% of the men reported smoking during the previous month, compared with 29% of the general male population of the U.S. Significant correlates of smoking among MSM included lesser education, depression and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among men solicited from mailing lists provided by gay organizations, 40% reported smoking during the previous year, which was associated with less education. 6 Among bar and telephone-recruited MSM in Oregon and Arizona, 48% of the men reported smoking during the previous month, compared with 29% of the general male population of the U.S. Significant correlates of smoking among MSM included lesser education, depression and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Higher rates of smoking among urban-dwelling lesbians and men who have sex with men (MSM) are suggested by a small number of studies, all from the United States. [3][4][5][6][7][8][9][10][11][12][13] A recent review article identified only three reports pertaining to smoking among MSM. 7 Including reports published subsequently, 4,8,9,[11][12][13] only two employed probability sampling to generate representative samples of MSM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature also clearly documents disparities in smoking among lesbian, gay, and bisexual populations (i.e., sexual minorities) in the United States, suggesting 50%-70% higher prevalence than the general population (Austin et al, 2004;Garofalo, Wolf, Kessel, Palfrey, & DuRant, 1998;Gruskin, Greenwood, Matevia, Pollack, & Bye, 2007;Lee, Griffin, & Melvin, 2009;McCabe, Boyd, Hughes, & d'Arcy, 2003;Skinner, 1994;Stall, Greenwood, Acree, Paul, & Coates, 1999;Tang et al, 2004). Moreover, the American Lung Association (2010) published a special report of tobacco disparities among sexual minorities, harkening a call for more research.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that lesbians and bisexual women may represent a subpopulation at especially elevated risk for the harmful health effects from alcohol and tobacco use (Bradford et al, 1994;Cochran, 2001;Cochran et al, 2000;Diamant et al, 2000;Fifield et al, 1975;Gruskin et al, 2001;Hughes and Eliason, 2002;Israelstam and Lambert, 1983;Peterson, 1989a, 1989b;Nardi, 1982;Roberts and Sorensen, 1999;Skinner, 1994;Skinner and Otis, 1996). Although findings observed across surveys of lesbians and bisexual women have not been entirely consistent (Bloomfield, 1993;Cochran et al, 2003;Roberts and Sorensen, 1999), typically women classified as lesbian or bisexual, as compared to heterosexual women, more commonly report being a current or former tobacco smoker (Bradford and Ryan, 1988;Cochran et al, 2001;Diamant and Wold, 2003;Diamant et al, 2000;Gruskin et al, 2001), appear less likely to abstain from alcohol consumption (Cochran et al, 2000;Diamant et al, 2000;Roberts and Sorensen, 1999), evidence a pattern of alcohol use that includes more frequent consumption as well as greater amounts drunk, though typically still within a moderate range (Diamant et al, 2000;Hughes and Eliason, 2002;Roberts and Sorensen, 1999), and perhaps fail to show normative age-related declines in alcohol use (Abbott, 1998;Bradford et al, 1994;Gruskin et al, 2001;Hughes and Wilsnack, 1997;Peterson, 1989a, 1989b).…”
Section: Introductionmentioning
confidence: 99%